2018
DOI: 10.1016/j.gore.2018.08.004
|View full text |Cite|
|
Sign up to set email alerts
|

Cervical cancer complicating pelvic organ prolapse, and use of a pessary to restore anatomy for optimal radiation: A case report

Abstract: Cervical cancer is the most common gynecologic malignancy worldwide and the third most common gynecologic cancer in the USA. Improved screening methods such as liquid-based cytology accompanied by Human Papilloma Virus (HPV) co-testing have contributed to a declining incidence of cervical cancer. There are approximately 13,000 new cases per year in the United States, accounting for 4200 deaths (Siegel et al., 2011). Pelvic organ prolapse increases with age, obesity and parity. In the absence of bothersome urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…As for the modifications which might occur at the level of a procident uterine cervix, ulceration is a frequently encountered finding; however, in all such cases biopsy of this lesion is needed in order to exclude the presence of a synchronous malignant transformation (23).…”
Section: Discussionmentioning
confidence: 99%
“…As for the modifications which might occur at the level of a procident uterine cervix, ulceration is a frequently encountered finding; however, in all such cases biopsy of this lesion is needed in order to exclude the presence of a synchronous malignant transformation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ER) and progesterone receptor (PR) are present on the surface of hormone target cells and are mainly distributed in targets such as uterus and cervix. These can specifically bind to corresponding hormones and play a role in regulating the occurrence and development of cervical squamous epithelial lesions [8,9] . Ki67 is a relatively positive sign of nuclear proliferation.…”
mentioning
confidence: 99%
“…Rarely, as seen in our patient, due to chronic irritation, primary vaginal cancer may develop secondary to prolonged POP. However, primary vaginal or cervical cancer and POP combination is rarely reported in the literature [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. The increase in the incidence of both POP and primary vaginal cancer with advancing age makes this combination more frequent in elderly people [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, using of pessary can also cause serious complications as bleeding and ulceration, and special care should be taken during this treatment [29]. Recently, Dawkins et al reported a case of 72-year-old woman with cervical cancer with POP, and she was treated with definitive CRT and BT [18]. Gelhorn pessary was placed and perineoplasty was performed before EBRT to reduce POP, and the authors reported no treatment-related side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation